Economic crisis and youth unemployment: The Greek case - Papadopoulos, Orestis (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2018)
Young people have been hard hit by the crisis and the austerity measures implemented in Greece since 2010. After six years of significant changes in the Greek employment and social system young people face burgeoning difficulties to find quality and well-paid jobs while the proliferation of flexible and insecure jobs has taken an epidemic form. This article presents the labour market reforms implemented in Greece and shows that these reforms have shifted the bargaining power in favor of employers as labour power has become rather cheap, flexible and adaptable. The narrative that flexibilization will assist economic growth and generate quality jobs seems to be fading away since most newly created jobs are temporary, part-time and low-paid. The dismantling of collective agreements and labour laws through which young employees used to guarantee some protection has meant that poverty, insecurity and deprivation have become persistent features of their social existence.